Improving literacy in Kapencar Village, Wonosobo, through the KKN Unsoed program - Kamaluddin, Ridlwan; Riski, Loliana; Ngatifah, Lutfi; Laili, Alya Sania; Putri, Amanda Aura; Leonardo, Leonardo; Esalka, Kautsar Ikraam (Jurnal Abmas, 2026)
Such literacy practices are often unpopular with students, especially children, because they are considered monotonous and uninteresting. Universitas Jenderal Soedirman implemented the Thematic Community Service Program (Kuliah Kerja Nyata or KKN) on Literacy in Kapencar Village to improve reading interest and literacy skills among the community, especially for children. The primary issue facing this village is a low literacy culture, mainly due to a lack of awareness about the importance of literacy. The program employed a participatory approach, utilizing the Participatory Action Research (PAR) model, which involved students, teachers, library managers, and village officials. Conducted over 35 days, the program engaged 435 kindergarten and elementary school students through five core activities: literacy visits, read-aloud sessions, book review exercises, story writing exercises based on reading materials, and empowering village libraries. The results indicated improvements in basic literacy skills, writing creativity, and students’ confidence in expressing ideas. Moreover, the village library became more actively visited by children for reading and borrowing books. Challenges included limited book collections, varying student abilities, and the short duration of activities. Nevertheless, the program successfully fostered a supportive literacy environment in Kapencar Village. For sustainability, it is recommended to establish literacy groups, strengthen collaboration with schools and libraries, and involve parents in encouraging reading habits at home.